2022
DOI: 10.48550/arxiv.2204.01471
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pulse-level Noise Mitigation on Quantum Applications

Siyuan Niu,
Aida Todri-Sanial

Abstract: Currently available quantum computers are prone to errors. Circuit optimization and error mitigation methods are needed to design quantum circuits to achieve better fidelity when executed on NISQ hardware. Dynamical decoupling (DD) is generally used to suppress the decoherence error and different DD strategies have been proposed. Moreover, the circuit fidelity can be improved by pulselevel optimization, such as creating hardware-native pulse-efficient gates. This paper implements all the popular DD sequences a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Grover's quantum search problem can be mapped to a time-optimal control problem, and then described through the Pontryagin Maximum Principle [387]. Furthermore, QOCT has been used to optimize drives in quantum algorithms such as QAOA [440] and quantum simulation, for example of a chiral effective-field theory [291] and of an extended Bose-Hubbard model [317].…”
Section: Quantum Algorithmsmentioning
confidence: 99%
“…Grover's quantum search problem can be mapped to a time-optimal control problem, and then described through the Pontryagin Maximum Principle [387]. Furthermore, QOCT has been used to optimize drives in quantum algorithms such as QAOA [440] and quantum simulation, for example of a chiral effective-field theory [291] and of an extended Bose-Hubbard model [317].…”
Section: Quantum Algorithmsmentioning
confidence: 99%
“…(4) What conditions lead to idle qubits and what is the strategy to insert DD to idle qubits under different conditions? The first question was discussed in [17], where the authors comprehensively evaluated the performance [5]. They demonstrated that DD performs better when applied to a subset of qubits rather than all.…”
Section: Related Workmentioning
confidence: 99%
“…These two techniques need a large overhead of tuning DD sequences with extra circuits. Recently, Niu et al reported the impact of different DD strategies on well-known quantum applications to provide insights for application-specific error mitigation using DD technique [17]. However, these previous methods only concentrate on application-level DD insertion instead of understanding and analyzing the conditions that lead to idle qubits, hence decoherence errors.…”
Section: Introductionmentioning
confidence: 99%